Preventive practices on sexually transmitted infections in men from the Cruz Blanca Chincha town center, March-June 2021 - Salvatierra-Hilares, Yanet Diana (2021)
Introduction: Sexually transmitted infections continues to be a public health concern at the International, National and local level, Men are exposed through sexual relations, being affected, which conditions to maintain the appearance of risks, exposing them to be victims of the hierarchy of infections. Objective: To determine the preventive practices on sexually transmitted infections in men of the Centro Poblado Cruz Blanca Chincha, March - June 2021. Materials and Methods: Applied: It is based on the verification of knowledge based on sexual practice between the level of knowledge and preventive measures, Descriptive: It only describes facts of reality related to preventive practices, Quantitative: It will measure and analyze through statistics the relationship between the notion and preventive practices, It will work with 171 men from the study population for research due to the programming assigned to the establishment. (20% of the male population from 18 to 59 years old), Preventive practices on sexually transmitted infections, The technique used was the survey in order to obtain information for the development of the research, The instrument called a questionnaire was applied, All the information of the questionnaire was collected, it will be processed manually and coded into an Excel spreadsheet, the database obtained will be processed using the statistical software SPSS Version 25, in order to obtain results. Results: It is observed the primary preventive practices that men have on STIs is Inadequate 30.99%, Indifferent 50.29% and only adequate 18.71%, Secondary preventive practices that men have on STIs is Inadequate 82, 46%, Indifferent 17.52% while the adequate ones is 0%. Conclusions: It was evidenced that men do not have preventive measures about sexually transmitted infections, which can lead to future infections, spread of infections.